Ethanolic Extract of Curcuma zedoaria Enhances Burn Wound Healing in Male White Rats - Yuliawati, Yuliawati; Kasmadi, Fathnur Sani; Elisma, Elisma; Dewi, Hasna; Afryandes, Amelya; Puteri, Vanya Gita (Sciences of Pharmacy, 2026)
In addition to its widespread use as a culinary spice, white turmeric rhizome (Curcuma zedoaria (Christm.) Roscoe) exhibits important pharmacological activities, including anti-inflammatory, anticancer, and antioxidant effects. The rhizome contains secondary metabolites such as flavonoids, alkaloids, saponins, phenols, tannins, and terpenoids, which are believed to contribute to its potential efficacy in treating burns. This study used a fully randomized post-test-only control group design consisting of five treatment groups: P1 (5% ethanol extract of white turmeric rhizome), P2 (10%), P3 (15%), K⁺ (positive control: Bioplacenton), and K⁻ (negative control: Vaseline flavum). Parameters observed included reduction in burn wound diameter and collagen density, which were assessed through histological analysis. The results showed significant differences between treatment groups (p < 0.05). The 10% concentration showed the highest wound healing activity, reaching a healing rate of 54.72% and producing denser collagen compared to the other treatments. However, its effect did not exceed the positive control (Bioplacenton). The 5% concentration showed moderate healing activity (43.84%) with intermediate collagen density, while the 15% concentration produced the lowest effect. Overall, the findings indicate that the ethanol extract of white turmeric rhizome, particularly at a concentration of 10%, enhances burn wound healing and increases collagen formation, supporting its potential as a natural therapeutic agent for the treatment of burns.